Maintaining sexuality in menopause. (March 2014) - Nappi, Rossella E; Martini, Ellis; Martella, Silvia; Capuano, Francesca; Bosoni, David; Giacomini, Sonia; Beraghi, Matteo; Spinillo, Arsenio
Sexual health in the menopause is a medical challenge because the progressive decline of sexual hormones interacts with the aging process and many psychosocial stressors modulate vulnerability for sexual symptoms (low sexual desire, poor arousal and lubrication, dyspareunia, orgasmic dysfunction and lack of satisfaction). In clinical practice, a coordinated approach is needed to optimally manage the risk for developing female sexual dysfunction (FSD), especially when chronic conditions are present. Biomedical and psychosocial interventions include general education, recognition of signs and symptoms, promotion of health, attention to the partner and individualization of treatment. Counselling to overcome personal and relational difficulties should be always combined with hormonal and non-hormonal strategies to maximize biological signals driving the sexual response. By enhancing women's abilities to cope with sexual changes at midlife, health care providers may significantly optimize healthy aging and partnership.